Heavy metal accumulation in a medicinal plant Centella asiatica from Peninsular Malaysia - Ong, Hock Ghim; Yap, Chee Kong; Mahmood, Maziah; Tan, Soon Guan (Asian Network for Scientific Information, 2011)
The objective of this research was to determine the metal accumulation of C. asiatica collected from 13 sampling sites from Peninsular Malaysia and its safety for consumption by the public in Malaysia. Centella asiatica plants were collected (or bought) from 13 sampling sites (9 from the wild and 4 from markets) between May and June of 2010. The leaves, stems and roots of C. asiatica were determined for Cadmium, Copper, Iron, Nickel, Lead and Zinc. Generally, Iron accumulation was the highest followed by Zinc, Lead, Copper, Nickel and Cadmium. For all metal accumulations, roots showed the highest level, followed by leaves and stems. Plants from sampling sites in Seremban, PPauh and Butterworth were higher in metal accumulation due to nearby activities such as industrial area and highway. When compared to the reference values from Recommended Dietary Allowance, Daily Dietary Intake, Tolerable Upper Intake Level and maximum level intake without detriment to health, all samples from the 13 sampling sites had metal levels which were within or lower than the safety levels or maximum permissible level for human consumption. Therefore, our results showed that Centella asiatica was safe to be consumed for all purposes especially for medical treatment of various illnesses.